Using distributive surface water and groundwater modelling techniques to quantify groundwater recharge and baseflow for the Verlorenvlei estuarine system, west coast, South Africa. - Watson, Andrew. P. (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2019.